An all-optical modulator based on a graphene–plasmonic slot waveguide at 1550 nm. (27th March 2019) - Sun, Feiying; Xia, Liangping; Nie, Changbin; Qiu, Ciyuan; Tang, Linlong; Shen, Jun; Sun, Tai; Yu, Leyong; Wu, Peng; Yin, Shaoyun; Yan, Shihan; Du, Chunlei
Abstract: An all-optical modulator with high modulation efficiency based on a graphene-plasmonic slot waveguide structure is proposed. The modulation efficiency is enhanced by the strong interaction between the light and the graphene–plasmonic structure. A modulation efficiency of 0.21 dB μ m −1 is obtained with the signal light at a wavelength of 1550 nm. A graphene–plasmonic slot waveguide device of length of 10 μ m is fabricated in the experiment. Benefiting from the strong modulation, it is a promising candidate as an on-chip optical modulator with high modulation efficiency and micrometer-scale footprint.